Aryl hydrocarbon receptor agonist diuron and its metabolites cause reproductive disorders in male marine medaka (Oryzias melastigma). (October 2022) - Zhou, Yixi; Zhu, Kongyang; Wang, Qian; Chen, Meng; He, Chengyong; Yang, Chunyan; Zuo, Zhenghong
Abstract: Diuron, a widely used phenylurea herbicide, has been frequently detected in marine organism and seawater all over the world. But the understanding of potential damage of diuron on reproduction in marine fish is currently not enough. Herein, marine medaka ( Oryzias melastigma ) were continuously exposed to 0, 5, 50, 500, and 5000 ng/L diuron from embryo (0 dpf) to adult (180 dpf) stage. The results suggested that diuron had an adverse influence on male reproduction for marine medaka, including decreased gonado somatic index, histological changes of testes, decreased mobility of sperm, and reduced fecundity through disrupting the balance of sex hormone and genes expression related to hypothalamus-pituitary-gonadal-liver (HPGL) axis. The reduced fecundity was reflected in abnormal sexual behaviors, further inhibited growth and development of F1 embryo and larvae. Moreover, the proportion of diuron metabolites (DCPMU and DCPU) was increased in fish, but the proportion of diuron was decreased with the increasing of exposure concentration. Diuron, DCPMU, and DCPU was identified as aryl hydrocarbon receptor agonist (AhR) agonist using in silico and in vivo models. DCPMU and DCPU induced the gene expression of AhR signaling and metabolizing enzymes (such as cyp1a1 ) in the livers. A great deal of major metabolites affected various organs related to HPGL axis of male marine medaka and led to serious reproductive disorders. Consequently, it reveals that long-term exposure to environmentally relevant concentrations of diuron and even AhR agonist pesticides pose a potential ecological risk for marine fish. Graphical abstract: Image 1 Highlights: Long-term exposure to diuron caused reproductive disorders. Diuron exposure disrupted hypothalamus-pituitary-gonadal-liver axis. Reproductive toxicity was mainly caused by diuron metabolites. Activation of AhR signaling pathway was induced by diuron and its metabolites.